2004
DOI: 10.1111/j.1365-2494.2004.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of Lolium rigidum Gaud. on the early growth of three associated pasture species

Abstract: In Mediterranean areas, the establishment of multispecies pastures for extensive livestock use is an alternative to the growing of traditional cereal crops. Lolium rigidum Gaud. is one of the most valuable forage grasses adapted to semiarid environments but its performance in mixtures is not fully understood. Field observations suggest that the species exerts allelopathic effects, although there is no evidence in the literature to support this assumption. The objective of the study was to determine whether L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
7
31
0
1
Order By: Relevance
“…The extract was diluted with distilled water to obtain concentrations of 3.4 and 10 g L -1 and these were stored in a refrigerator at 4°C. These extract concentrations were chosen in order to simulate plant material left in the field after a low and high productive year, respectively (Emeterio et al 2004). These concentrations are similar to those used by Fernandez et al (2006) in a study involving P. halepensis about its potential allelopathic effect in the secondary succession.…”
Section: Materials Collectionmentioning
confidence: 99%
“…The extract was diluted with distilled water to obtain concentrations of 3.4 and 10 g L -1 and these were stored in a refrigerator at 4°C. These extract concentrations were chosen in order to simulate plant material left in the field after a low and high productive year, respectively (Emeterio et al 2004). These concentrations are similar to those used by Fernandez et al (2006) in a study involving P. halepensis about its potential allelopathic effect in the secondary succession.…”
Section: Materials Collectionmentioning
confidence: 99%
“…Kong et al (2002) discovered that Ageratum conyzoides L. under water deficit and nutrient stress showed strong allelopathic potential. Emeterio et al (2004) observed that the inhibitory allelopathic effect of Lolium rigidum Gaud. on the root growth of other plants increased under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…O potencial alelopático do sistema radicular tem baixa atividade, quando comparado a parte aérea (WANDSCHEER; PASTORINI, 2008), podendo em alguns casos ocorrer estímulo no desenvolvimento inicial de algumas espécies, L. multiflorum, Dactylis glomerata e Medicago sativa (EMETERIO; ARROYO;CANALS, 2004).Quando comparado o potencial alelopático das partes das plantas, para cada cultura, de modo geral, na média das concentrações dos extratos da planta inteira e parte aérea, excluindo as testemunhas, reduziram em 27 e 54% a germinação, comparativamente ao sistema radicular (Tabela 2).…”
Section: Fonte: Elaboração Dos Autoresunclassified